1996
DOI: 10.1074/jbc.271.33.20192
|View full text |Cite
|
Sign up to set email alerts
|

Bcl-2 Protects Macrophages from Nitric Oxide-induced Apoptosis

Abstract: Endogenously generated or exogenously supplied nitric oxide (NO)-induced apoptotic cell death in the mouse macrophage cell line RAW 264.7. Apoptotic signaling caused an early accumulation of the tumor suppressor p53 prior to DNA fragmentation. Contrary to the notion of specific activating signals, inhibitory transduction mechanisms largely remain unknown. Therefore, RAW 264.7 macrophages were stably transfected with human Bcl-2, an anti-apoptotic protein. Bcl-2 transfectants showed substantial protection from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
108
0

Year Published

1998
1998
2006
2006

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 216 publications
(113 citation statements)
references
References 31 publications
5
108
0
Order By: Relevance
“…Although little is yet known regarding the functional significance of Bax and Bcl-2 expression in the microglial/macrophage lineage, marked changes in the pattern of their expression are likely to alter the life span of these reactive macrophages. Evidence of the role of Bax/ Bcl-2 families in the apoptotic pathway of macrophages/monocytes has been recently studied in human atherosclerotic plaques, giant cell granulomas and osteopetrosis (35)(36)(37)(38)(39)(40). It is possible that these macrophages, after engulfing the degraded myelins, undergo apoptosis, and apoptotic macrophages may further enhance the development of demyelinating lesions by releasing cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…Although little is yet known regarding the functional significance of Bax and Bcl-2 expression in the microglial/macrophage lineage, marked changes in the pattern of their expression are likely to alter the life span of these reactive macrophages. Evidence of the role of Bax/ Bcl-2 families in the apoptotic pathway of macrophages/monocytes has been recently studied in human atherosclerotic plaques, giant cell granulomas and osteopetrosis (35)(36)(37)(38)(39)(40). It is possible that these macrophages, after engulfing the degraded myelins, undergo apoptosis, and apoptotic macrophages may further enhance the development of demyelinating lesions by releasing cytokines.…”
Section: Discussionmentioning
confidence: 99%
“…-mediated apoptosis in RAW 264.7 macrophages (Albina et al, 1996;Messmer et al, 1996b). We observed enforced expression of human Bcl-2 in RAW macrophages, named Rblc2-14, that contained the plasmid pRc/CMVbcl2 (Figure 3a).…”
Section: P53 Acts Upstream Of Bcl-x L and Mitochondrial Cyt C Releasementioning
confidence: 91%
“…p53 antisense transfection and Bcl-2 overexpression in RAW 264.7 macrophages Construction of p53 antisense expressing RAW 264.7 cells (RDp53asn-11) and Bcl-2 overexpressing RAW 264.7 cells (Rbcl2-14) were previously described (Messmer and BruÈ ne, 1996a;Messmer et al, 1996b).…”
Section: Cell Culturementioning
confidence: 99%
See 1 more Smart Citation
“…[25][26][27] It has been reported that NO is directly involved in apoptosis of cells via several mechanisms, including inhibition of mitochondrial respiration, inhibition of DNA synthesis and initiation of DNA strand breaks. 28,29 Our experiments revealed that when S-nitrosoacetylpenicillamine (SNAP), an NO donor, was added into the SCCVII culture in vitro, the apoptosis of the SCCVII cells was induced. Furthermore, apoptotic tumor cells adjacent to iNOS-positive immune cells in vivo were observed.…”
Section: Discussionmentioning
confidence: 99%